Purificação, caracterização e avaliação da atividade antiproliferativa de um inibidor de quimotripsina tipo kunitz de semente de Eryhrina velutina - Lucena, Sheila Varela (2010)
A chymotrypsin inhibitor was purified from Erythrina velutina seeds by ammonium sulphate fractionation, affinities chromatographies on Trypsin-Sepharose, Quimotrypsin-Sepharose and reversed phase C-18 FPLC/AKTA system. The inhibitor, named EvCI, shown molecular mass of 17 kDa, as determined by SDSPAGE. 2D-PAGE showed four isoinhibitors with pI values of 4,42, 4,63, 4,83 and 5,06, with molecular mass of 17 kDa each. The aminoacid sequence of EvCI was determined by MALDI-TOF-MS and showed a high similarity with other Kunitz-type inhibitor of Erythrina variegata. EvCI competitively inhibited chymotrypsin, with Ki of 4 x10-8 M, but did not inhibited trypsin, pancreatic elastase, bromelain and papain. The inhibitory activity of EvCI was stable over wide pH and temperature ranges. In the presence of DTT 100 mM for 120 min, EvCI lost 50 % of activity. Cytotoxicity was studied in HeLa, MDA, HepG2, K562 and PC3 cells after 72-h incubation period. EvCl inhibited HeLa cells growth with an IC50 value of 50 μg/ml. Subsequent studies in HeLa cells analysis of cell death by annexin V/PI double-staining and cell cycle, using flow cytometry. The results provide evidence for a cytostatic activity of EvCl and support further studies on potential application of this inhibitors as an antiproliferative agent in combined therapy against cervical cancer